PENGARUH DISIPLIN KERJA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI DI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK, PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DP3APPKB) BANTUL DIY.: PENGARUH DISIPLIN KERJA DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI DI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK, PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DP3APPKB) BANTUL DIY - nurkholi fatulhaq; Endah Wening Budiningrum (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2025)
This study aims to explain the partial and simultaneous effects of work discipline and work facilities on employee performance at the Office of Women's Empowerment and Child Protection, Population Control, and Family Planning. Issues related to work discipline and work facilities can disrupt employee performance. This is a quantitative study because it uses measurement methods and samples to test variables and hypotheses. Data was collected using questionnaires and observations. The researcher conducted several tests, including validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, t-tests, F-tests, multiple linear regression analysis, and determination coefficient tests. The population in this study consisted of all 61 employees at the Office of Women's Empowerment and Child Protection, Population Control, and Family Planning. The results of this study indicate that work discipline has a partial and significant effect on employee performance. Work facilities have a partial and significant effect on employee performance. Work discipline and work facilities have a simultaneous effect on employee performance.